2017
DOI: 10.1093/jisesa/iex002
|View full text |Cite
|
Sign up to set email alerts
|

On the Molecular Basis of Division of Labor in Solenopsis invicta (Hymenoptera: Formicidae) Workers: RNA-seq Analysis

Abstract: The fire ant Solenopsis invicta Buren is an important invasive pest. Among S. invicta workers behavioral changes depend on age where younger ants are nurses and older ants foragers. To identify potential genes associated with this division of labor, we compared gene expression between foragers and nurses by high-throughput sequencing. In total, we identified 1,618 genes significantly differently expressed between nurses and foragers, of which 542 were upregulated in foragers and 1,076 were upregulated in nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…, the nursing area) as compared with the foraging area; 2 ) in nurses of Solenopsis invicta 9 cytochrome P450 4C1 transcripts were found to be down-regulated (69), similar to what we found in IP-KD ants (Supplemental Figs. 8 and 9); and 3 ) isolated, single nurses of Camponotus rufiper exhibit higher locomotor activity as compared with foragers (56).…”
Section: Discussionsupporting
confidence: 80%
“…, the nursing area) as compared with the foraging area; 2 ) in nurses of Solenopsis invicta 9 cytochrome P450 4C1 transcripts were found to be down-regulated (69), similar to what we found in IP-KD ants (Supplemental Figs. 8 and 9); and 3 ) isolated, single nurses of Camponotus rufiper exhibit higher locomotor activity as compared with foragers (56).…”
Section: Discussionsupporting
confidence: 80%
“…In ants however, despite the broad correlative evidence for brood carers harbouring more lipid storages than foragers [69,14,94,95], clear transcriptomic signatures of nutritional status have so far not been found [30,31]. Only a single study identified lipid storage and fatty acid metabolism to be enriched functions of genes differentially expressed between brood carers and foragers [96]. In that study however, transcriptomes of young brood carers and old foragers were compared.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional analyses, such as GO enrichment, WGCNA and metabolic pathway comparisons are commonly used and provide valuable insights into broader patterns of gene expression [27,30,31,67,68,75,87,90,96]. Hence, results and conclusions depend on the number and identity of large sets of genes, and partly their FDR values and raw read counts provided as an input.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between age, physiology and behavioural specialization is well documented and widespread across the social Hymenoptera, a consensus on the underlying transcriptomic signatures and expression biases of individual candidate genes linked to worker specialization is lacking. For instance, while the transition from brood care to foraging is associated with a strong reduction in body fat reserves in multiple species (Ament et al, ; Bernadou, Busch, & Heinze, ; Porter & Jorgensen, ; Robinson, Feinerman, & Franks, ; Schulz, Huang, & Robinson, ; Toth, Bilof, Henshaw, Hunt, & Robinson, ; Toth, Kantarovich, Meisel, & Robinson, ; Toth & Robinson, ; Tschinkel, ), behaviour‐specific transcriptomic signatures of nutrition‐related and metabolic processes were found in some studies but not in others (Alaux et al, ; Ament, Corona, Pollock, & Robinson, ; Daugherty, Toth, & Robinson, ; Feldmeyer, Elsner, & Foitzik, ; Khamis et al, ; Manfredini et al, ; Qiu, Zhao, & He, ). Information on nutritional status is conveyed via the target of rapamycin and insulin/insulin‐like signalling (IIS) pathways (Ament et al, ; Maestro, Cobo, & Bellés, ; Morton, Cummings, Baskin, Barsh, & Schwartz, ; Nilsen et al, ; Rodrigues & Flatt, ), which interact with juvenile hormone (JH) and the yolk protein precursor Vitellogenin (Vg) (Libbrecht et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistency across studies in the association between gene expression and worker task choice may reflect species‐specific mechanisms regulating behavioural specialization or differences across studies regarding experimental design. Gene expression patterns associated with behavioural specialization of workers are typically identified by comparing brood carers and foragers that not only differ in behaviour but also in age and fertility (Cardoso‐Júnior et al, ; Feldmeyer et al, ; Ingram et al, ; Johnson & Jasper, ; Khamis et al, ; Manfredini et al, ; Qiu et al, ; Scheiner, Entler, Barron, Scholl, & Thamm, ; Zhao et al, ), two factors that are linked to gene expression (Alaux et al, ; Feldmeyer et al, ; Harrison, Hammond, & Mallon, ; Lucas, Romiguier, & Keller, ; Nilsen et al, ; Whitfield, Cziko, & Robinson, ). Not experimentally controlling for age or fertility (in species with potentially fertile workers) when contrasting brood carer and forager transcriptomes could thus lead to confounded data sets and the identification of transcriptomic patterns being linked to any of the three factors or combinations thereof.…”
Section: Introductionmentioning
confidence: 99%